Quality-adjusted time without symptoms of disease or toxicity (Q-TWiST) analysis of fruquintinib + best supportive care (BSC) compared with placebo + BSC in metastatic colorectal cancer (mCRC): Results from the FRESCO-2 trial - Tabernero, Josep; Satoh, Taroh; Dasari, Arvind; Lonardi, Sara; Eng, Cathy; Garcia-Carbonero, Rocio; Elez, Elena; Yoshino, Takayuki; Sobrero, Alberto F.; Yao, James C.; Kasper, Stefan; Arnold, Dirk; et al. (Journal of clinical oncology, 2024)
116Background: As mCRC and its treatment can adversely impact quality of life (QoL), maintaining QoL is an important treatment goal in addition to improving survival outcomes, particularly as patients progress through lines of therapy. In the global, randomized, double-blind, phase 3 FRESCO-2 trial (NCT04322539), fruquintinib (F) + BSC vs placebo (P) + BSC demonstrated significantly improved overall survival (OS) (median 7.4 months vs 4.8 months; HR 0.66, 95% confidence interval [CI] 0.55-0.80) and progression-free survival, with a manageable safety profile and without deterioration of QoL in heavily pretreated patients with refractory mCRC. The objective of this post-hoc Q-TWiST analysis was to assess the quality-adjusted survival benefit of F + BSC in the context of the FRESCO-2 trial. Methods: The Q-TWiST analysis was applied to all 691 randomized patients from FRESCO-2 (F + BSC n=461 vs P + BSC n=230). Survival time of each patient was partitioned into 3 health states: time spent with treatment-emergent adverse events of CTCAE grade 3 or 4 before disease progression (TOX), time before disease progression without toxicity (TWiST), and time between disease progression and death or censoring (REL). Assuming utility coefficients of 1 for TWIST and 0.5 for TOX and REL, Q-TWiST was calculated as the utility-weighted sum of the time spent in each health state. The mean time spent in each of the 3 health states was calculated for each treatment group using Kaplan-Meier analysis, and a 95% CI for the difference between treatment was calculated using the nonparametric bootstrap method. Results: Q-TWiST was 6.25 months for F + BSC and 4.21 months for P + BSC, a difference of 2.04 (95% CI 1.51-2.57) months longer with F + BSC vs P + BSC. This difference in Q-TWiST was mainly driven by the difference in the TWiST component (2.14 months [95% CI 1.78-2.49]; F + BSC 4.06 months vs P + BSC 1.92 months). The relative Q-TWiST gain, calculated as the difference in Q-TWiST divided by the mean OS time of the P + BSC group, was 31.4% in favor of F + BSC. Conclusions: In the FRESCO-2 trial, F + BSC demonstrated a clinically meaningful quality-adjusted survival benefit compared with P + BSC in heavily pretreated patients with refractory mCRC. Clinical trial information: NCT04322539.